2013
DOI: 10.1016/j.cortex.2012.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The differential consolidation of perceptual and motor learning in skill acquisition

Abstract: Implicit skill learning is an unconscious way of learning which underlies not only motor but also cognitive and social skills. This form of learning is based on both motor and perceptual information. Although many studies have investigated the perceptual and motor components of "online" skill learning, the effect of consolidation on perceptual and motor characteristics of skill learning has not been studied to our knowledge. In our research we used a sequence learning task to determine if consolidation had the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
61
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 43 publications
8
61
1
Order By: Relevance
“…Hence, our comments on this particular topic are only speculative. All we are saying is that, given our present results, it would appear that offline consolidation does not play a major role in implicit sequence OFFLINE CONSOLIDATION 28 learning, at least not in the sense of further "silent" improvement (Hallgato et al, 2013;Németh & Janacsek, 2011;Németh et al, 2010;Siengsukon & Boyd, 2009;Spencer et al, 2007).…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…Hence, our comments on this particular topic are only speculative. All we are saying is that, given our present results, it would appear that offline consolidation does not play a major role in implicit sequence OFFLINE CONSOLIDATION 28 learning, at least not in the sense of further "silent" improvement (Hallgato et al, 2013;Németh & Janacsek, 2011;Németh et al, 2010;Siengsukon & Boyd, 2009;Spencer et al, 2007).…”
Section: Discussionmentioning
confidence: 52%
“…For example, it has been demonstrated that the performance of some procedures can be significantly improved after a "silent" or offline interval subsequent to training. During this interval, there is no further practice, or even mention, of the procedure, and learning remains largely tacit or implicit (Brown & Robertson, 2007;Hallgato, Gyori-Dani, Pekar, Janacsek, & Nemeth, 2013;Krakauer & Shadmehr, 2006;Németh et al, 2010). Consolidation is also sometimes referred to as resistance to interference and forgetting (Ghilardi, Moisello, Silvestri, Ghez, & Krakauer, 2009;Goedert & Willingham, 2002; Stephan, Meier, Orosz, Cattapan-Ludewig, & KaelinLang, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations